The Relationship of Perceived Health Benefits and Information Sources to Following a Gluten-Free Diet Among People Without Celiac Disease or Non-Celiac Gluten Sensitivity. (29th May 2020) - Arslain, Kristina; Baishya, Pratiksha; Gustafson, Christopher; Rose, Devin
Abstract: Objectives: The gluten-free diet (GFD) has been adopted by many people who do not have Celiac disease or non-Celiac gluten sensitivity, but no studies examine the relationship of perceived health benefits of, and the sources that recommend trying, the GFD to the decision to follow the diet. Methods: We surveyed a large, nationally representative sample of 3051 US residents about their attitudes, perceptions, and experiences with the GFD. Logistic regression was used to compare respondents who had no diagnosed need for a GFD but were currently avoiding or had avoided gluten previously (GF-Consumer) to the consumers that had never tried a GFD. Results: Over one-fifth of our respondents were GF-Consumers. Beliefs that "a gluten-reduced diet is healthier for people than a full-gluten containing diet" (OR 1.55; P < 0.01), that "gluten-free products are generally more nutritious than their gluten-containing variant" (OR 1.53; P < 0.01) and that a GFD can help clear acne (OR 1.44; P < 0.01) were all positively associated with trying a GFD. The most influential source that suggested the diet was oneself who learned about a GFD through personal research (OR 3.35; P < 0.01). This was followed by "family member or friend" (OR 2.68; P < 0.01) and "healthcare center or health professional (doctor, dietitian, etc.)" (OR 2.10; P < 0.01). Conclusions: Positive, but scientifically unsubstantiated, beliefs about the benefits of the GFD were strongly associated with trying a GF diet. Both conventional and unconventional sources of information about the GFD were positively associated with following the diet. These findings about beliefs and information sources highlight potential barriers to the promotion of scientifically based nutritional recommendations to consumers. Funding Sources: University of Nebraska Agricultural Research Division Innovation Fund for Wheat/Cereal Crops.